Decarbonization in Maritime Technology: A Scoping Review of Alternative Fuels, Energy Systems, and Policy Pathways Toward Net-Zero Shipping - Ayuba John Buba; Isaac John Ibanga (The Indonesian Institute of Science and Technology Research, 2026)
The decarbonization of the maritime sector represents a complex socio-technical transition rather than a purely technological shift, requiring the alignment of fuels, energy systems, and regulatory frameworks. Despite rapid innovation, the field remains fragmented, with competing technological pathways and limited integration across system levels. Guided by the targets of the International Maritime Organization, this study conducts a scoping review of literature published between 2020 and 2025 to critically examine how decarbonization strategies are conceptualized, developed, and operationalized. Using the PRISMA-ScR approach, this review synthesizes evidence across four interrelated domains: alternative fuels, energy efficiency technologies, electrification and hybrid systems, and digital optimization. Rather than identifying a dominant solution, the analysis reveals a persistent trade-off between technological maturity, scalability, and environmental impact. The findings highlight a systemic misalignment between technological innovation and supporting infrastructure, as well as a lack of integrated frameworks that connect engineering solutions with policy mechanisms. This review advances the literature by proposing an integrative perspective that reframes maritime decarbonization as a multi-layered transition problem, emphasizing cross-domain interoperability and policy-technology co-evolution. It identifies critical research gaps in hybrid energy systems, infrastructure readiness, and techno-economic scalability, and outlines a future research agenda centered on system integration and global implementation pathways toward net-zero shipping.